2013
DOI: 10.1182/blood-2013-05-501494
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic capacity of M1- and M2-polarized macrophages is determined by the levels of TIMP-1 complexed with their secreted proMMP-9

Abstract: Key Points• Acquisition of high angiogenesis-inducing capacity by human and murine macrophages requires their polarization toward the M2 phenotype.• M2-polarized macrophages shutdown their TIMP1 gene expression and initiate production of highly angiogenic TIMP-deficient proMMP-9.A proangiogenic function of tissue-infiltrating monocytes/macrophages has long been attributed to their matrix metalloproteinase-9 zymogen (proMMP-9). Herein, we evaluated the capacity of human monocytes, mature M0 macrophages, and M1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
187
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(198 citation statements)
references
References 50 publications
11
187
0
Order By: Relevance
“…Similar to previously published findings [56], we also observed that PLN increased the number of TAMs, and this effect was prevented by PLN-alen, although these findings did not reach statistical significance probably due to the small sample size (Supplemental Fig. S5).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to previously published findings [56], we also observed that PLN increased the number of TAMs, and this effect was prevented by PLN-alen, although these findings did not reach statistical significance probably due to the small sample size (Supplemental Fig. S5).…”
Section: Resultssupporting
confidence: 90%
“…It was recently reported that PLN significantly enhanced tumor growth in a murine model of cancer and this was associated with diminished T-cell functionality and tumor infiltration [56], suggesting inhibition of antitumor immunity. We theorized that mechanisms of PLN-induced tumor growth involve immunosuppressive leukocytes such as tumor-associated macrophages (TAM) since macrophages have been implicated as key players in both the pharmacology of carrier-mediated therapies [10,37] and in cancer progression [21,43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations